The stingless bee species Trigona spp. on various species of flowering plants in Baturaja City, Ogan Komering Ulu District, South Sumatra - Febriani, Elsa; Pujiastuti, Yulia (Journal of Smart Agriculture and Environmental Technology, 2023)
Trigona bee (Trigona spp.) is a species of honey-producing bee that does not have a sting (Stingless bees). This bee is small in size and plays an important role as a pollinator of flowering plants. Research was conducted from June to July 2021 in Baturaja City, Ogan Komering Ulu Regency, South Sumatra. The purpose of this research was to study the species of Trigona bees (Trigona spp.) visiting various flowering plants and the species of flowering plants visited by these bees. The research method involved purposive sampling and direct observation in the field. Observations were made by identifying bee species present on several flower plants. Trigona bees predominantly used plants in the flowering phase as a food source due to their abundant nectar and pollen production. The field observations revealed 11 species of flowering plants favored by Trigona bees, namely Kembang kertas (Zinnia elegans), Jambu air (Syzygium aqueum), Air mata pengantin (Antigonon leptopus), Kelengkeng (Dimocarpus longan), Melinjo (Gnetum gnemon), Cabai (Capsicum annuum), Seri (Muntingia calabura), Palem (Dypsis lutescens), Matahari (Helianthus annuus), Santos lemon (Xanthostemon chrysanthus), and Belimbing (Averrhoa carambola). The most commonly found species of Trigona spp. was Heterogona itama, observed on the bridal tears flower (Antigonon leptopus).